Penerapan Reduced Impact Logging Dalam Perencanaan Pemanenan Hutan Di Hutan Hujan Tropis Indonesia - Muamar Kadafin; Alfian Pujian Hadi; Imam Syaukani; Akbar Al Imam (Yayasan Tajuk Indonesia, 2024)
The Indonesian forests occupied the third area in the world with tropical forests as well as donations of rainforests in Kalimantan and Papua. Currently, wood is still the prima in a forestry sector so that the highest income generated by the forest comes to wood shoppers. The destructive logging process can cause damage to the environment. Forest harvesting planning needs to be carried out as an effort to reduce the impact of soil or the upright damage caused by logging. In addition, the use of Reduced Impact Logging (RIL) techniques in forest harvesting are other solutions to reduce the impact of the damage caused by for harvesting activities. This paper is made with the aim of knowing the influence of the use of RIL engineering on the impact of damage caused by forest harvesting activities in tropical rainforests in Indonesia. Data collection is conducted using the literature study method, while the data analysis techniques used are the analysis method for obtaining valid inference and can re-check the context. The results of the literature study indicate that the forest harvesting planning system used in the Indonesian Tropical Rainforests is composed of strategik planning, operational planning, and task planning. Forest harvesting techniques used in the Indonesian Tropical Rainforests consist of Conventional Logging (CL) and Reduced Impact Logging (RIL). The application of RIL techniques has a positive impact on the environment, as it can reduce the upright rate of damage, reducing the level of carbon mass reduction caused by forest harvesting, as well as from the aspects of RIL-eating financial analysis of wood-eating analysis, better than conventional wooden wasteers if the wooden-eating waste is calculated.